The Divine Comedy by Dante, Illustrated, Hell, Volume 10 - Dante Alighieri, 1265-1321; Doré, Gustave, 1832-1883; Cary, Henry Francis, 1772-1844 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Divine Comedy by Dante, Illustrated, Hell, Volume 10" by Dante Alighieri is an Italian narrative poem begun around 1308 and completed around 1321. This epic work follows Dante's journey through the three realms of the afterlife: Hell, Purgatory, and Heaven. Guided first by the Roman poet Virgil and later by Beatrice, Dante encounters divine justice as souls receive punishment or reward for their earthly actions. The poem allegorically represents the soul's journey toward God, drawing on medieval Catholic theology and philosophy. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Divine_Comedy
Release date is 2004-08-07
Produced by David Widger
Keywords: Hell -- Poetry; Epic poetry, Italian -- Translations into English; Italian poetry -- To 1400 -- Translations into English